2022
DOI: 10.7306/gq.1662
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of elements in vegetation spontaneously developing on self-heating waste dumps in the Upper Silesia area (Poland)

Abstract: Ac cu mu la tion of el e ments in veg e ta tion spon ta ne ously de vel oping on self-heat ing waste dumps in the Up per Silesia area (Po land). Geo log i cal Quar terly, 66: 30,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…It is a low-cost and sustainable remediation method used worldwide to eliminate toxic substances from individual elements of the environment-soil, water and air-using selected plant species [39,40], which use different phytomechanisms when phytoremediating pollutants [41]. Also, some species appearing in burning coal-wasted dumps in Poland can accumulate concentrations of selected elements, which has been confirmed in numerous studies [42][43][44]. In the Upper Silesian Coal Basin, such plants include, e.g., Solidago canadensis-Canadian goldenrod [45,46] and Calamagrostis epigejos-wood small-reed [47,48]-dominant species in many dumps [24].…”
Section: Introductionmentioning
confidence: 84%
“…It is a low-cost and sustainable remediation method used worldwide to eliminate toxic substances from individual elements of the environment-soil, water and air-using selected plant species [39,40], which use different phytomechanisms when phytoremediating pollutants [41]. Also, some species appearing in burning coal-wasted dumps in Poland can accumulate concentrations of selected elements, which has been confirmed in numerous studies [42][43][44]. In the Upper Silesian Coal Basin, such plants include, e.g., Solidago canadensis-Canadian goldenrod [45,46] and Calamagrostis epigejos-wood small-reed [47,48]-dominant species in many dumps [24].…”
Section: Introductionmentioning
confidence: 84%
“…Com par ing with data for the pre sum ably fire-free heap hab i tats stud ied by Rahmonov et al (2020), we found a higher de gree of pH variabil ity than their 4.1-5.9 range, though our pH data usu ally plotted around 7, in part due to en rich ment in organonitrogen species. Wojewódka-Przyby³ et al (2022) found a high vari a tion (CV>100%) in el e men tal con tent be tween the sam ples. The most com mon anom a lies in the CWHs stud ied con cern Zn, Pb and Hg -de pend ing on waste type -fol lowed by Bi, U and Tl.…”
Section: Introductionmentioning
confidence: 84%
“…For the cur rent study, geo chem i cal data on 11 veg e ta tion sam ples char ac ter ized by Wojewódka-Przyby³ et al (2022) were used. They come from a burn ing mixed (coal-smelter) waste heap in the D¹browa Miejska dis trict of Bytom (Rumex crispus L., Arctium tomentosum Mill., Verbascum -river bank; Solidago canadensis L. and Verbascum -heap top; Tussilago farfara L.post-smelter slag zone; Betula pendula Roth and Populus L.burn ing es carp ment), the "Ruda" heap in Zabrze-Bis kupice (Solanum nigrum L. -or ganic-and S-rich fumaroles), and the "Ajska" post-smelter heap in OEwiêtoch³owice-Chro paczów (Eupatorium cannabinum L.).…”
Section: Study Area and Methodology Vegetation And Soil Samplesmentioning
confidence: 99%
See 2 more Smart Citations